The Rhyacophila fasciata Group in Western Europe: Confirmation of Rhyacophila denticulata McLachlan 1879 (stat. prom.) and Rhyacophila sociata Navás 1916 (stat. res.), based on morphological and molecular genetic evidence (Trichoptera: Rhyacophilidae) - Valladolid, María; Arauzo, Mercedes; Basaguren, Ana; Dorda, Beatriz A.; Rey, Isabel (Zootaxa, 2018)
In order to check the presence and distribution of Rhyacophila fasciata fasciata Hagen 1859 (species described from Austria) and R. fasciata denticulata McLachlan 1879 in the Iberian Peninsula, we studied the morphology of Spanish, French, and Austrian specimens, together with their mitochondrial cytochrome c oxidase (mtCOI). We observed that the individuals considered to date as R. fasciata denticulata are in fact two different species: R. denticulata, presently known from France and possibly in some rivers of the Basque Country (Spain), and R. sociata Navás 1916 distributed in Spain and France. These two species are also different from the reference species (R. fasciata) from Austria, so we propose a change in the taxonomic status of R. fasciata denticulata to R. denticulata (stat. prom.) and the restoration of R. sociata (stat. res.), with the designation of a neotype, due to the loss of the holotype.